Lessons learned from one decade of developing agent-based tools for traffic modeling, simulation, and control: how to make cities smarter - Bazzan, Ana L. C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
While there is no definitive agenda for making cities smarter in terms of mobility, intuition says that information is key. However, contrarily to a more technical view, information should not only be consumed by the users, but also produced by them. This is already happening (smart-phones, social networks) but is far from being exploited by technical systems related to transportation. In this paper I discuss some of the issues related to more human-centered transportation system. It is argued that users of this system are somehow influencing it with their increasing coupled behaviors. Thus, there is a real opportunity for changing the paradigm in order to take advantage of the collective intelligence.